Comparison of The Accuracy of Contour Data in Photogrammetric and Terrestrial Surveys - Saputra, Hendra; Rizki, Roma; Sastra, Marhadi (UI Scholars Hub, 2024)
Understanding and accurately representing the Earth's surface is crucial in various scientific and practical fields. Over the past decades, measurement technology has seen remarkable advancements, offering an array of methods for recording and analyzing Earth's surface with increasing precision and efficiency. Two primary approaches have risen to the forefront of this field: the Digital Terrain Model (DTM) and terrestrial measurements using a Total Station. Although both technologies offer unique advantages and constraints, a comprehensive direct comparison between these two methods often remains an underexplored area. The Digital Elevation Model (DEM) represents the height of the ground surface resulting from acquisition using drones. Ground Control Points (GCPs) are evenly distributed in the study’s Area of Interest (AoI) to enhance accuracy and precision. The DEM data is then converted into contour maps and corrected for horizontal and vertical accuracy using the Root Mean Square Error (RMSE) method following the Geospatial Information Agency's standards (Regulation No. 15 of 2014). Terrestrial measurement is a method used to create contour maps using a Total Station to obtain field coordinate data. Terrestrial measurements create contour maps using a Total Station, with field coordinate data corrected by GPS Geodetic methods and compared with aerial photo DEM data. RMSE calculations reveal that DEM data has RMSExy of 0.319 meter (m) and RMSEz of 0.197 m, whereas terrestrial data using the Total Station shows RMSExy of 0.062 m and RMSEz of 0.039 m. Accuracy comparisons indicate that the DEM from aerial photographs has a Circular Error (CE) of 0.485 m and Linear Error (LE) of 0.325 m, while terrestrial data accuracy using a Total Station shows CE of 0.094 m and LE of 0.064 m.